Neuroleptic Malignant Syndrome Caused by a Combination of Carbamazepine and Amitriptyline - A. Bruce Janati; Naif ALGhasab; Aboubaker Osman (Case Reports in Neurological Medicine)
A 32-year-old female, with a history of secondarily-generalized convulsive epilepsy, mental retardation, and a psychiatric illness, developed neuroleptic malignant syndrome while receiving carbamazepine and amitriptyline concurrently. We hypothesize that the addition of amitriptyline to carbamazepine caused a decrease in the serum level of carbamazepine, resulting in NMS. We conclude that combination therapy with carbamazepine and amitriptyline should be avoided in patients who are predisposed to NMS. The purpose of this paper is to warn physicians against combination therapy with carbamazepine and tricyclic antidepressants which may be conducive to neuroleptic malignant syndrome in susceptible patients.